1995
DOI: 10.3354/meps119167
|View full text |Cite
|
Sign up to set email alerts
|

Filling a gap:dynamics of space occupancy on a mussel-dominated subtropical rocky shore

Abstract: The mussel Sernirnytilus algosus (Gould) often dominates the space on exposed rocky shores of subtropical South America. Dynamics of space occupancy was investigated in a rocky intertidal habitat in central Peru. A series of colonization expenrnents and quantitative sampling of musselassociated faunas were conducted to clarify interspec~f~c relationships anlong resident organisms. Spatial gaps created within the S. algosus zone were colonised successively by the barnacles Jehlius cirratus (Darwin) and Notochth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 14 publications
5
82
1
Order By: Relevance
“…Conversely, organisms with closely similar body sizes are more likely to compete for resources. In particular, interference competition for space is widespread among sessile organisms (Connell 1961, Paine 1984, Williamson 1990, Tokeshi & Romero 1995. The present study has demonstrated that 2 sessile organisms, the goose barnacle Capitulum mitella and the mussel Septifer virgatus, can coexist in the upper intertidal, despite having similar body sizes and similar modes of resource utilization (space and food; in particular, habitable space on microhabitat scales is limited in the upper intertidal).…”
Section: Coexistence In Similar-sized Sessile Organismsmentioning
confidence: 92%
See 1 more Smart Citation
“…Conversely, organisms with closely similar body sizes are more likely to compete for resources. In particular, interference competition for space is widespread among sessile organisms (Connell 1961, Paine 1984, Williamson 1990, Tokeshi & Romero 1995. The present study has demonstrated that 2 sessile organisms, the goose barnacle Capitulum mitella and the mussel Septifer virgatus, can coexist in the upper intertidal, despite having similar body sizes and similar modes of resource utilization (space and food; in particular, habitable space on microhabitat scales is limited in the upper intertidal).…”
Section: Coexistence In Similar-sized Sessile Organismsmentioning
confidence: 92%
“…At the same time, the commonness and importance of positive interactions in species coexistence have been increasingly recognised with critical evaluation in a wide range of natural communities in both marine and terrestrial habitats (Bertness & Callaway 1994, Callaway 1995, Bruno et al 2003. In marine systems, mussels (Suchanek 1985, Witman 1987, Tokeshi & Romero 1995, seaweeds (Dayton 1975, Menge 1978a,b, Thompson et al 1996, Bertness et al 1999) and seagrasses (Heck & Orth 1980, Stoner & Lewis 1985, Irlandi & Peterson 1991 have been frequently identified as habitat-modifying organisms that can influence the success of associated organisms by modifying physically and/or biologically stressful conditions (e.g. thermal stress : Dayton 1975, Hawkins 1981, Bertness et al 1999, Leonard 1999; low nutrient levels : Williams 1990; disturbance: Bertness & Grosholz 1985;predation: Heck & Orth 1980, Witman 1987.…”
Section: Introductionmentioning
confidence: 99%
“…Increased abundances and/or diversities within mussel beds have been reported for a variety of mussel species, including Mytilus californianus (Kanter 1980) (Stephenson & Stephenson 1972, Peake & Quinn 1993. It has also been fo.und that species outcompeted for primary space by mussels can live epizoically on the mussel shells (Lohse 1993, Tokeshi & Romero 1995. Even beds created by zebra mussels Dreissena polymorpha benefit populations of a wide variety of small invertebrates (Dermott 1992, Stewart & Haynes 1994.…”
Section: Discussionmentioning
confidence: 99%
“…On marine rocky shores, primary rock surfaces are frequently occupied by dense popul a t i o n~ of mytilid bivalves (cf. Seed 1976, Suchanek 1985, Seed & Suchanek 1992 which form an intricate matrix of 3-dimensional habitat structures that can be inhabited by polychaetes and other organisms (Suchanek 1979, 1985, Tsuchiya & Nishihira 1985, 1986, Tsuchiya & Bellan-Santini 1989, Tokeshi & Romero 1995a. These organisms constitute a unique assemblage, as the majority of taxa cannot exist without the protection provided by mussel beds on a n exposed shore (Tokeshi & Romero 1995a).…”
Section: Introductionmentioning
confidence: 99%
“…Seed 1976, Suchanek 1985, Seed & Suchanek 1992 which form an intricate matrix of 3-dimensional habitat structures that can be inhabited by polychaetes and other organisms (Suchanek 1979, 1985, Tsuchiya & Nishihira 1985, 1986, Tsuchiya & Bellan-Santini 1989, Tokeshi & Romero 1995a. These organisms constitute a unique assemblage, as the majority of taxa cannot exist without the protection provided by mussel beds on a n exposed shore (Tokeshi & Romero 1995a). Although a considerable body of information exists on the dynamics of mussel beds in both intertidal (Dayton 1971, Paine 1971, 1974, Paine & Levin 1981 and subtidal (Dean & Hurd 1980, Schoener & Schoener 1981, Chalmer 1982, Greene & Schoener 1982, Okamura 1986) systems, few studies have investigated the spatial patterns and interspecific relationships of species coexisting in these mussel-matrix habitats (Tsuchiya & Nishihira 1985, 1986, Tokeshi et al 1989b).…”
Section: Introductionmentioning
confidence: 99%